If a quadratic equation `ax^2+bx+c = 0` has roots `r1` and `r2` then we can say;

`r1+r2 = (-b)/a`

`r1xxr2 = c/a`

Similarly for `x^2-px+q=0` we can write;

`alpha+beta = -p`

`alphaxxbeta = q`

If the quadratic equation which has roots `alpha(alpha+beta)` and `beta(alpha+beta)` represent by `x^2+mx+n =...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

If a quadratic equation `ax^2+bx+c = 0` has roots `r1` and `r2` then we can say;

`r1+r2 = (-b)/a`

`r1xxr2 = c/a`

Similarly for `x^2-px+q=0` we can write;

`alpha+beta = -p`

`alphaxxbeta = q`

If the quadratic equation which has roots `alpha(alpha+beta)` and `beta(alpha+beta)` represent by `x^2+mx+n = 0` then we can say;

`-m = alpha(alpha+beta)+beta(alpha+beta)`

`n = alpha(alpha+beta)xxbeta(alpha+beta)`

`alpha(alpha+beta)+beta(alpha+beta)`

`= (alpha+beta)(alpha+beta)`

`= (alpha+beta)^2`

`= (-p)^2`

`= p^2`

Hence;

`-m = p^2 `

`m = -p^2`

`alpha(alpha+beta)xxbeta(alpha+beta)`

`= (alpha+beta)^2xx(alphaxxbeta)`

`= (-p)^2xx(q)`

`= p^2q`

Hence;

`n = p^2q`

**So the quadratic equation that has roots as `alpha(alpha+beta)` and `beta(alpha+beta)` can be given by;**

`x^2-p^2x+p^2q = 0`

**Further Reading**